Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 5 - Section 5.4 - Polynomials in Several Variables - Exercise Set: 3

Answer

$-47$

Work Step by Step

Substituting $x=2$ and $y=-3$, the given expression, $ xy^3-xy+1 ,$ evaluates to \begin{array}{l}\require{cancel} (2)(-3)^3-(2)(-3)+1 \\\\= (2)(-27)-(-6)+1 \\\\= -54+6+1 \\\\= -48+1 \\\\= -47 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.